Siring success in kangaroos: size matters for those in the right place at the right time. (19th March 2020) - Montana, Luca; Rousseu, François; Garant, Dany; Festa-Bianchet, Marco
Abstract: In polygynous species, male reproductive success is predicted to be monopolized by a few dominant males. This prediction is often not supported, suggesting that ecological and alternative mating tactics influence siring success. The spatiotemporal distribution of individuals and the number of males competing for each receptive female are often overlooked because they are difficult to monitor in wild animals. We examined how spatial overlap of female–male pairs, the time spent by a male on the breeding site, number of competitors, and morphological traits influence siring probability in eastern gray kangaroos ( Macropus giganteus ). We compared home range overlap for 12 208 dam–male pairs and 295 known dam–sire pairs to define local competitive groups and to estimate every male's opportunity to sire the young of each female. We compared models considering morphological traits relative to the entire population or to local competitive groups. Including local competition improved model performance because it estimated the intensity of competition and compared each male's morphological traits to those of its competitive group. Regardless of size, males can increase their probability to sire a young by increasing their mating opportunity relative to the mother. We underline the importance of considering spatial structure to assess the intensity of competition in species where males cannot equally access all females in a population. The estimation of mating opportunity and intensity of local competition improves our understanding of how morphological traits affect siring success when each mating event involves a different set of competing males, a characteristic of most wild species. Abstract : In polygynous species, large males have higher mating success but, to mate with a given female, they also need to be in the right place at the right time. In kangaroos, males do not share space with all females in a population. Thus, a male can increase his reproductive success by increasing the overlap between his home range and that of a female, regardless of body size and condition.